2005
DOI: 10.1080/01443610400023163
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, hostility and hysterectomy

Abstract: Sixty-five women (aged 32 - 54 yrs) were assessed at 2 months before to 8 months after total abdominal hysterectomy on four separate occasions. Beck's Depression Inventory (BDI), Taylor's Manifest Anxiety Scale (TMAS), the Buss-Durkee Hostility Inventory (BDHI), Measurement of Masculinity-Femininity (MF), Likert scales and semantic differentials for psychological, somatic and sexual factors varied as assessment tools. High-dysphoric and low-dysphoric women were compared with regard to hysterectomy outcomes. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 3 publications
1
18
2
3
Order By: Relevance
“…The powerful social factors affecting the reactions of women after hysterectomy are indicated as the educational status, income level, cultural structure, age at hysterectomy, short decision period before the operation, little support from the spouse and existence of a mental disorder preoperatively [14]. In our study, no relationship was found between age groups and the level of anxiety (p > .05) (Tablo 4).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The powerful social factors affecting the reactions of women after hysterectomy are indicated as the educational status, income level, cultural structure, age at hysterectomy, short decision period before the operation, little support from the spouse and existence of a mental disorder preoperatively [14]. In our study, no relationship was found between age groups and the level of anxiety (p > .05) (Tablo 4).…”
Section: Discussioncontrasting
confidence: 49%
“…It was concluded in some studies that preoperative anxiety levels were high; however, the nursing approach and instructions given are effective in reducing the level of anxiety [14-16]. Ozdemir and Pasinlioglu (2009) found in their study on 34 study group cases and 32 control group cases undergoing hysterectomy with benign causes that while the average state anxiety score was 40.9 ± 6.3, it fell to 27.6 ± 3.7 in the postoperative period (p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the strong desire for a child in nulliparous women in this population. Ewalds-Kvist et al [22] also reported that married nulliparous women experienced more severe depression after hysterectomy.…”
Section: Discussionmentioning
confidence: 96%
“…It was considered as the second common surgical operation among women of reproductive age after cesarean section. [2,3] The most common reasons for hysterectomy are conditions like excessive bleeding, uterine leiomyomas, endometriosis, adenomyosis, uterine prolapse, Pelvic Inflammatory Disease, and cancer of the reproductive tract. [4] Hysterectomy clients are bound to feel more stress because no other surgical procedure has such significant meaning to women involving alteration in their reproductive organ.…”
Section: Introductionmentioning
confidence: 99%